Local and Parallel Finite Element Algorithms for the Navier-Stokes Problem (Journal of Computational Mathematics, 2006)
Based on two-grid discretizations, in this paper, some new local and parallel finite element algorithms are proposed and analyzed for the stationary incompressible Navier-Stokes problem. These algorithms are motivated by the observation that for a solution to the Navier-Stokes problem, low frequency components can be approximated well by a relatively coarse grid and high frequency components can be computed on a fine grid by some local and parallel procedure. One major technical tool for the analysis is some local a priori error estimates that are also obtained in this paper for the finite element solutions on general shape-regular grids.
Keywords: Navier-Stokes problem; Finite element; Two-grid method; Local and parallel algorithm.